2016
DOI: 10.1530/jme-15-0227
|View full text |Cite
|
Sign up to set email alerts
|

SIDT2 is involved in the NAADP-mediated release of calcium from insulin secretory granules

Abstract: The Sidt2 global knockout mouse (Sidt2 −/− ) has impaired insulin secretion. The aim of this study was to assess the role of SIDT2 protein in glucose-induced insulin secretion in primary cultured mouse β-cells. The major metabolic and electrophysiological steps of glucose-induced insulin secretion of primary cultured β-cells from Sidt2 −/− mice were investigated. The β-cells from Sidt2 −/− mice had normal NAD(P)H responses and K ATP and K V currents. However, they exhibited a lower [Ca 2+ ] i peak height when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Sidt2‐deficient mice express reduced levels of the SNARE proteins synap1 and synap3 indicating that Sidt2 and SNAREs are directly involved in insulin secretion . Furthermore, the intracellular calcium signaling was changed in primary pancreatic β‐cells, this effect could be reversed by bafilomycin connecting intracellular calcium signaling to lysosomes . Application of nicotinic acid adenine dinucleotide phosphate (NAADP) rescued the calcium response although the islets of Sidt2‐deficient mice synthesized NAADP normally.…”
Section: Discussionmentioning
confidence: 99%
“…Sidt2‐deficient mice express reduced levels of the SNARE proteins synap1 and synap3 indicating that Sidt2 and SNAREs are directly involved in insulin secretion . Furthermore, the intracellular calcium signaling was changed in primary pancreatic β‐cells, this effect could be reversed by bafilomycin connecting intracellular calcium signaling to lysosomes . Application of nicotinic acid adenine dinucleotide phosphate (NAADP) rescued the calcium response although the islets of Sidt2‐deficient mice synthesized NAADP normally.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies have observed physiological effects of SIDT2 where the relationship to RNA transport, if any, is unclear. For example, mice lacking SIDT2 demonstrate impaired glucose tolerance, decreased serum insulin levels, and defective insulin secretion (Chang et al., 2016, Gao et al., 2013, Yu et al., 2015). Two recent studies also demonstrated that Sidt2 −/− mice develop non-alcoholic fatty liver disease (Chen et al., 2018, Gao et al., 2016), with one suggesting that this is due to induction of endoplasmic reticulum stress (Gao et al., 2016) and the other proposing that it is the result of defective autophagy (Chen et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…NAADP is a potent signaling molecule produced during β-cell glucose metabolism [ 280 ] that binds to unidentified NAADP-sensitive sites to elicit Ca 2+ release from intracellular stores, including the SG, during GSIS [ 31 , 281 ]. SIDT2 is located on insulin SGs and may mediate this mechanism [ 281 ]. Whole-body SIDT2 KO mice are glucose intolerant and have an insulin secretory defect [ 282 ].…”
Section: Luminal Components Of the Insulin Secretory Granulementioning
confidence: 99%